The Power Imbalance Personified: A Mixed-Methods Analysis of Senior-to-Junior Bullying in Indonesia's Medical Residency Programs - Alex Putra Pratama; Henry Clifford; Ahmad Erza; Ericca Dominique Perez; Fakhrul Setiobudi; Dedi Affandi; Lestini Wulansari; Fachrudin Sani; Vita Amanda; Zahra Amir (Enigma in Education, 2025)
Bullying within medical residency is a pervasive global issue with severe consequences for residents' mental health and patient safety. In Indonesia, where hierarchical structures in medicine are deeply entrenched, senior-to-junior bullying is a significant yet under-investigated problem. This study aimed to analyse the prevalence, forms, and lived experiences of bullying perpetrated by senior residents against their junior counterparts in Indonesian medical residency programs. A sequential explanatory mixed-methods design was employed. In the quantitative phase, an anonymous online survey was distributed to 584 junior medical residents across five major teaching hospitals in Indonesia. The survey included the validated Negative Acts Questionnaire-Revised (NAQ-R) and questions on demographics and specialty. In the qualitative phase, 25 junior residents who reported high levels of bullying were purposively selected for in-depth, semi-structured interviews to explore their experiences. Quantitative data were analysed using descriptive and inferential statistics, while qualitative data were subjected to reflexive thematic analysis. Quantitatively, 81.3% (n=475) of junior residents reported experiencing at least one bullying behaviour weekly. The most common forms were work-related, such as excessive workloads and meaningless tasks, and personal humiliation. Year of residency was significantly associated with bullying exposure. Qualitatively, four major themes emerged: (1) ‘The Hierarchy as an Unassailable Mandate for Abuse’; (2) ‘The Pedagogy of Fear: Bullying as a Misguided Educational Tool’; (3) ‘Silent Suffering and the Armour of Complicity’; and (4) ‘The Perpetuating Cycle: Victims on a Trajectory to Becoming Perpetrators’. The qualitative findings revealed that bullying was often rationalised by seniors as a necessary part of medical training. In conclusion, senior-to-junior bullying is alarmingly prevalent and deeply embedded in the culture of Indonesian medical residency programs. It is personified through a profound power imbalance, rationalised as an educational necessity, and sustained by a culture of silence. Urgent, multi-level interventions focusing on systemic change, faculty training, and robust confidential reporting systems are imperative to dismantle this destructive cycle.